2004
DOI: 10.1016/s0004-9514(14)60110-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of efficacy of McKenzie therapy for spinal pain

Abstract: A systematic review of randomised clinical trials was conducted to investigate the efficacy of McKenzie therapy in the treatment of spinal pain. Databases searched included DARE, CINAHL, CENTRAL, EMBASE, MEDLINE and PEDro. To be eligible for inclusion trials had to provide treatment according to McKenzie principles and report on one of the following outcomes: pain, disability, quality of life, work status, global perceived effect, medication use, health care contacts, or recurrence. Six trials were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(138 citation statements)
references
References 40 publications
4
126
0
8
Order By: Relevance
“…This approach was recommended in the original classification system, 35 leading to 3 categories based on the centralizing movement (flexion, extension, or a lateral shift). Two recent systematic reviews 27,85 have pooled data from 6 randomized or quasi-experimental studies investigating the effects of treatment provided according to principles proposed by McKenzie, a large component of which is repeated end-range movement in the direction of centralization. 91 These reviews found greater reductions in pain and disability for treatments based on McKenzie principles in the short term, but the differences were small in magnitude and no longer significant at long-term followup.…”
Section: Management Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was recommended in the original classification system, 35 leading to 3 categories based on the centralizing movement (flexion, extension, or a lateral shift). Two recent systematic reviews 27,85 have pooled data from 6 randomized or quasi-experimental studies investigating the effects of treatment provided according to principles proposed by McKenzie, a large component of which is repeated end-range movement in the direction of centralization. 91 These reviews found greater reductions in pain and disability for treatments based on McKenzie principles in the short term, but the differences were small in magnitude and no longer significant at long-term followup.…”
Section: Management Considerationsmentioning
confidence: 99%
“…91 These reviews found greater reductions in pain and disability for treatments based on McKenzie principles in the short term, but the differences were small in magnitude and no longer significant at long-term followup. 27,85 Studies included in these reviews used broad inclusion criteria, which may explain the small treatment effects. The reviews also included only studies with treatments provided according to McKenzie principles.…”
Section: Management Considerationsmentioning
confidence: 99%
“…35 The percentage of patients classified into the stabilization category was reported by Brennan et al as 24%. 21 Preliminary efficacy evidence exists for both MDT and TBC classification systems 30,38 as well as classifying patients based on CPR and CEN for treating patients with low back pain. 11,16,21,32,35 However, there are no published studies examining outcomes between patients classified according to McKenzie syndromes, PPC, and CPR categories, which may partially explain why there is a lack of agreement between clinicians and researchers on which classification treatment method works best for which patients.…”
Section: Introductionmentioning
confidence: 99%
“…The overall positive or negative change may be hard to discern from individual studies. For example, Clare et al 15 used a metaanalysis to examine the treatment effect of McKenzie therapy for spinal pain. Three studies supported the use of McKenzie therapy for short-term pain.…”
Section: Why Meta-analysismentioning
confidence: 99%